Pengaruh jenis media tanam dan konsentrasi nutrisi AB-MIX terhadap pertumbuhan selada hijau (Lactuca Sativa L.) menggunakan sistem hidroponik rakit apung - Pambudy, Bagas; Susanto, Anang; Wuryantoro (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Lettuce (Lactuca sativa L.) is a type of vegetable that is rich in vitamins A, B, and C. Lettuce leaves can not only be used as raw vegetables and decorations, but also have a fairly high economic value. Findings: Hydroponics has the potential to increase cultivation opportunities in Indonesia, especially due to the increasing market demand for chemical-free vegetables. In addition, with the reduction in productive land, climate change and unfavorable environmental conditions, as well as critical land problems, the application of hydroponic cultivation is becoming increasingly relevant. In Indonesia, lettuce production in 2017 was 627,611 tons, in 2018 lettuce production was 625,132 tons, in 2019 lettuce production was 638,731 tons and in 2020 it increased with lettuce production of 663,832 tons. Methods: This study was conducted using a 2-factor Randomized Block Design (RBD). Conclusion: There is an interaction between AB-Mix concentration treatment and planting media on the parameters of plant length 7 hst and number of leaves 7 hst. However, there is no interaction on the parameters of plant length 14 hst, 21 hst, 28 hst, number of leaves 14 hst, 21 hst, 28 hst, leaf area, fresh weight, root length, dry weight. The treatment of 1300 ppm concentration and rockwool planting media showed the highest average value on the growth of green lettuce. The concentration treatment factor significantly affected the number of leaves 7 hst, 14 hst, 21 hst, leaf area and fresh weight, but did not significantly affect the length of the plant 7 hst, 14 hst, 21 hst, 28 hst, number of leaves 28 hst, root length, dry weight. The treatment factor of planting media significantly affected all treatment parameters, namely plant length, number of leaves, leaf area, root length, fresh weight, dry weight.